Edukasi dan Motivasi Pemeliharaan Kesehatan Rongga Mulut dengan Sikat Gigi Kustom Modifikasi pada Siswa SLB YPAC Surabaya - Soesilo, Diana; Akwan, Yulie Emilda; Syanti, Wanda Rahma (LPPM Institut Pendidikan Nusantara Global, 2025)
SLB YPAC Surabaya is a school for students with disabilities, particularly those with cerebral palsy, who experience motor limitations and therefore require specially adapted tools for maintaining oral health. To support oral hygiene, a three-sided toothbrush was used, allowing simultaneous cleaning of the buccal, occlusal, and lingual/palatal surfaces, with the handle modified using child-safe clay that is inexpensive, easy to shape, and readily available. Oral hygiene was assessed using plaque index scores with a plaque detector and halitosis scores with a halitosis detector, and both students and their assistants were taught how to create the customized toothbrush handle. Parents’ knowledge was measured through pre- and post-tests, while students’ oral health was evaluated through plaque and halitosis indices. Wilcoxon tests showed significant differences in parental knowledge (p=0.000) and in plaque and halitosis scores before and after using the modified toothbrush (p=0.002; p<0.05), indicating clear improvement. Therefore, the use of a three-sided toothbrush with a clay-based customized handle is effective in enhancing the oral hygiene of students with cerebral palsy.